Effect of CEO power on Malaysian firm performance - Wong Yin Theng, Hooy Chee-Wooi, (Universiti Pendidikan Sultan Idris, 2017)
Effect of CEO power on Malaysian firm performance by Wong Yin Theng, Hooy Chee-Wooi,